(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
This scientific article examines some aspects of the history of culture and statehood of Khorezm. The Khorezm region has a rich historical and cultural heritage and is a region that created a unique civilization. Conclusions and recommendations are developed on the basis of scientific analysis.